Utility of mid arm circumfrence in identifying protein energy malnutrition in anganwadi children of 1 to 5 years of age in urban areas of Chamarajanagara district - Raghavendra, D; Senapathi , Pradeep; Kuldeep, G B; Goudar, Siddarth (International journal of health sciences, 2022)
Background: UNICEF reports that 53% of the Indian children are malnourished125. Early detection of malnourishment among preschool children helps to decrease the mortality and morbidity rate. Easy, economical and reliable anthropometric measures are required to detect the nutritional status among children in the community. Studies conducted in India found that prevalence of malnutrition in Anganwadi children ranges from 40 to 60%. Understanding the gravity of the problem, the present study was undertaken in and around Chamarajangara . Objective: Utility Of Mid Arm Circumference In Identifying Protein Energy Malnutrition In Anganwadi Children Of 1 To 5 Years Of Age. Materials and Methods: A cross sectional study was conducted in the urban areas of Chamarajanagara district in Karnataka from January 2020 to December 2021. All the children who were enrolled in the all the anganwadi centers in Chamarajanagara urban were included in the study. A total of 1000 children were included in the study . The data was collected by using a pre tested and semi structured questionnaire by Clinical examination and by anthropometry Measurement as per standards.